Politeness in requests to supervisors in emails / Ali Hallajian - Hallajian, Ali (2014)
This study investigates the politeness/impoliteness of supervisees’ request e-mails to their supervisors at a research university in Malaysia. It aimed at determining how Iranian post-graduate students formulate requests when writing e-mails to their Malaysian supervisors. The research aimed to determine if these requests were direct or indirect and if internal/external modification was used. These modifiers are used to mitigate or aggravate the imposition force of a request. The aim of the research was to determine how polite or impolite Malaysian supervisors perceived these requests. This data consists of 128 emails from 20 Iranian post-graduate students to their Malaysian supervisors. 20 supervisors were provided a questionnaire which was designed, pilot-tested. To achieve the objectives of the study, the move structures in request e-mails to their supervisors were first identified (Baugh, 2011). Next, Economidou-Kogetsidis’s (2011) framework which is based on Blum- Kulka et al. (1989) and Biesenbach-Lucas (2006, 2007) was used to determine the level of directness of requests and the internal and external modifications used. The results show that 14 types of generic elements might occur in the e-mails. The findings suggest that request e-mails usually composed of 4 moves which comprise of obligatory and optional steps within them. This result is in sharp contrast with the findings of Bough (2011). Iranian students mostly tend to use ‘Direct’ and ‘Conventionally Indirect’ requests in their e-mails. More specifically, the use of ‘Query Preparatory’ was very prevalent. However, the analysis of the questionnaire indicates that Malaysian supervisors perceive ‘Conventionally Indirect’ strategy as polite whereas ‘Direct’ strategy as an impolite one. ‘Politeness Marker ‘please’’, ‘Downtoners’ and ‘Time intensifier’ were the most used internal modification. In this case, supervisors confirm that if a student uses internal modifications (especially ‘Consultative devices’ and ‘Politeness Marker ‘please’’) in their e-mails they would be considered polite. Students employ ‘Salutation’, ‘Closing’ and ‘Pre-closing/ Thanks’ external modifications to a great extent which were in line with supervisors’ perception of politeness.